Equilibrium Price - Modelling, Forecast and Application - Sobiechowska-Ziegert, Aneta (Cena równowagi - modelowanie, prognoza i zastosowanie, 2010)
Modern economy is characterized by growing importance of prices. The knowledge of the general rules of price mechanism and price researches allows enterprises for foreseeing the equilibrium price and making profitable decisions, especially on the market in a homogeneous oligopoly, where entrepreneurs have to take competitors’ reaction into account. An econometric dynamic model of gasoline equilibrium prices, on the market of liquid fuel in Poland, enables to determine the factor elasticity of gasoline prices and seasonal effects. It also allows for constructing the accurate, conditional, short-run gasoline prices forecast.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 91, s. 125-135
Keywords: equilibrium price; forecasting; fuel prices